A Third Dose of an Inactivated Vaccine Dramatically Increased the Levels and Decay Times of Anti-SARS-CoV-2 Antibodies, but Disappointingly Declined Again: A Prospective, Longitudinal, Cohort Study at 18 Serial Time Points Over 368 Days - Liang, Xian-Ming; Xu, Qiu-Yan; Jia, Zhi-Juan; Wu, Meng-Juan; Liu, Yan-Yun; Lin, Li-Rong; Liu, Li-Li; Yang, Tian-Ci (Frontiers in Immunology, 2022)
Background: Due to anti-SARS-CoV-2 antibody decay and SARS-CoV-2 variants, vaccine booster doses are a constant concern. It was focused on whether the third dose can quickly evoke and activate immunity and produce a sufficient and durable immune protection. Objectives: To evaluate the responses and durations of five subsets of anti-SARS-CoV-2 antibodies and their predictive values for protection after the administration of a three-dose inactivated SARS-CoV-2 vaccines regimens. Methods: A prospective cohort study of five subsets of anti-SARS-CoV-2 antibodies (neutralizing antibody, anti-RBD total antibody, anti-Spike IgG, anti-Spike IgM, and anti-Spike IgA) was carried out to evaluate the efficacies and immune characteristics of a three-dose inactivated SARS-CoV-2 vaccines regimen in 32 volunteers. The dynamic response and immune decay were longitudinally profiled at 18 serial time points over 368 days. Results: The neutralizing antibody, anti-RBD total antibody, anti-Spike IgG and anti-Spike IgA levels rapidly increased to 773.60 (380.90-1273.00) IU/mL, 639.30 (399.60-878.60) AU/mL, 34.48 (16.83-44.68) S/CO and 0.91 (0.35-1.14) S/CO, respectively, after the administration of the third dose. Compared to the peak value after the second dose, these values were increased by 4.22-fold, 3.71-fold, 1.01-fold and 0.92-fold. On the other hand, the half-lives of the neutralizing antibody, anti-RBD total antibody, and anti-Spike IgG were 56.26 (95% CI, 46.81 to 70.49) days, 66.37 (95% CI, 54.90 to 83.88) days, and 82.91 (95% CI, 63.65 to 118.89) days, respectively. Compared to the half-lives after the second dose, these values were increased by 1.71-fold, 2.00-fold, and 2.93-fold, respectively. Nevertheless, the positive conversion rate of anti-Spike IgM was decreased to 9.38% (3/32), which was much lower than that after the second dose (65.63% (21/32)). Conclusions: Compared to the second dose, the third dose dramatically increased the antibody levels and decay times.. However, the half-life of neutralizing antibody remained unsatisfactory. Due to decay, a fourth dose, and even annual revaccination, might be considered in the SARS-CoV-2 vaccination management strategy.